James Madison : liberty's advocate - Madison, James, 1751-1836 (Word portraits of America's founder, 2018)
"Lists quotations by and about Madison, from his early life to accounts of him after his death. Also includes a brief biography and chronology of Madison's life, plus a list of identifications of the people mentioned."--Provided by publisher.